Editorial - Nesterak, Janusz; Ziębicki, Bernard (Journal of Public Governance, 2023)
In this special issue of Public Governance, five scientific articles have been published, presenting research results within selected contemporary problems of public management. These articles were prepared and presented within the 14th International Scientific Conference of the College of Management and Quality Sciences, titled “Knowledge – Economy – Society”, which took place on 26–27 October, 2022. These works have been chosen out of elaborations submitted to the conference. The problem area of these articles refers both to the functioning of public organisations and to the perspective of the state’s public policies. The problem area concerns Poland as well as other countries of Europe.